Disparities in Spawning Times Between in situ and ex situ Pillar Corals - Neely, Karen L.; Lewis, Cindy L.; Macaulay, Kevin A. (Frontiers in Marine Science, 2020)
Contrasts in spawning time between in situ and ex situ colonies of the pillar coral Dendrogyra cylindrus were assessed by comparing 8 years of in situ spawning observations with 3 years of observations on ex situ corals held in outdoor flow-through tanks. In situ colonies exhibited a 3-day spawning window, with peak spawning occurring three nights after the full moon and 90 (males) – 96 (females) min after sunset. The ex situ spawning window extended across 7 days, with a peak on nights 4–5 after the full moon; females continued to spawn through night 8. Ex situ spawning occurred ∼50 min later than in situ spawning, and the spawning window for ex situ females was significantly greater than for in situ colonies. Fragments held ex situ for as few as 10 days experienced delayed spawning times, but corals held for greater than one lunar year exhibited significantly later spawning than those held less than one lunar year. Early and late full moons resulted in earlier male spawn time and asynchronous gamete release between males and females. Comparing spawn times throughout the Caribbean identified distance from lighted shorelines as a strong correlate with spawn time in minutes after sunset; proximity to artificial light resulted in delayed spawn times. We propose that artificial lights are red-shifting the twilight spectrum and affecting corals’ perception of lighting cues that trigger spawning. Coral colonies held at outdoor ex situ facilities, which are subject to even higher levels of artificial light, exhibit even further asynchrony in spawning time as well as spawning night. The effects of widespread and increasing light pollution on spawning synchrony may represent a potential stressor that could inhibit natural reef recovery.